The influence of anti-VEGF therapy on binocular vision in patients with age-related macular degeneration - Uzdrowska, Marta; Bilińska, Ewa; Broniarczyk-Loba, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Purpose : To assess binocular vision quality in patients with age-related macular degeneration and to evaluate the effect of the treatment on binocular vision in these patients. Material and methods : Subjective visual acuity, simultaneous perception, fusion and stereopsis were assessed before anti-VEGF treatment and after the third intravitreal injection in 24 patients with neovascular age-related macular degeneration. Results : Most patients (66.7%) had partially preserved binocular vision and 1/3 of the group presented with suppression. Some patients with suppression gained partial binocular vision after treatment, whereas others, presenting with some degree of binocular vision before treatment, lost it after therapy. Anti-VEGF treatment caused a change in the refractive error in 50.0% of the group, and a change of a dominant eye in 3 patients. Strabismus was diagnosed in 25.0% of patients. Treatment-related improvement of visual acuity was not equivalent to the qualitative improvement in binocular vision. Conclusion : The anti-VEGF therapy has a significant impact on binocular vision in treated patients. However, impairment of central vision in age-related macular degeneration does not affect all levels of binocular vision, so visual acuity testing before and after treatment cannot be the only predictor of changes in binocularity. Thus, a standard vision examination in patients treated with anti-VEGF agents should be extended to include binocular vision assessment.